Anabolic Heterogeneity Following Resistance Training: A Role for Circadian Rhythm? - Camera, Donny M. (Frontiers in Physiology, 2018)
It is now well established that resistance exercise stimulates muscle protein synthesis and promotes gains in muscle mass and strength. However, considerable variability exists following standardised resistance training programs in the magnitude of muscle cross-sectional area and strength responses from one individual to another. Several studies have recently posited that alterations in satellite cell population, myogenic gene expression and microRNAs may contribute to individual variability in anabolic adaptation. One emerging factor that may also explain the variability in responses to resistance exercise is circadian rhythms and underlying molecular clock signals. The molecular clock is found in most cells within the body, including skeletal muscle, and principally functions to optimise the timing of specific cellular events around a 24 h cycle. Accumulating evidence investigating the skeletal muscle molecular clock indicates that exercise-induced contraction and its timing may regulate gene expression and protein synthesis responses which, over time, can influence and modulate key physiological responses such as muscle hypertrophy and increased strength. Therefore, the circadian clock may play a key role in the heterogenous anabolic responses with resistance exercise. The central aim of this Hypothesis and Theory is to discuss and propose the potential interplay between the circadian molecular clock and established molecular mechanisms mediating muscle anabolic responses with resistance training. This article begins with a current review of the mechanisms associated with the heterogeneity in muscle anabolism with resistance training before introducing the molecular pathways regulating circadian function in skeletal muscle. Recent work showing members of the core molecular clock system can regulate myogenic and translational signaling pathways is also discussed, forming the basis for a possible role of the circadian clock in the variable anabolic responses with resistance exercise.